Sonographic diagnosis of spontaneous uterine rupture at the site of cornual wedge resection scar – a case report. Issue 1 (February 2014) - Wye, Deborah; Magotti, Robert; Al‐Mashat, Dheya; Benzie, Ronald; Condous, George
Abstract: Introduction : Uterine rupture and uterine dehiscence during pregnancy are known complications of a scarred uterus. Spontaneous uterine rupture at the site of prior cornual wedge resection has been previously reported in the literature, however remains rare. Discussion : We present a case of uterine rupture at 30 weeks gestation. This woman had previous right sided interstitial pregnancy treated with uncomplicated laparoscopic cornual wedge resection at eight weeks gestation. The index pregnancy occurred eight months after surgery. An emergency ultrasound prompted by non‐specific abdominal pain and tenderness at 30 weeks gestation enabled diagnosis of uterine dehiscence. At emergency caesarean section four hours later full thickness wall rupture and haemoperitoneum were found. Surgical intervention resulted in a good outcome for both mother and baby. Conclusion : A brief account on uterine rupture in late pregnancy and relevant sonographic features related to this case are presented. This case demonstrates the value of ultrasound in the assessment of subtle clinical signs and symptoms in patients at risk of uterine rupture.